1990
DOI: 10.1002/j.1460-2075.1990.tb07376.x
|View full text |Cite
|
Sign up to set email alerts
|

OP-1 cDNA encodes an osteogenic protein in the TGF-beta family.

Abstract: Amino acid sequences of two tryptic peptides derived from enriched bovine osteogenic protein preparations revealed considerable homology to two members of the TGF‐beta (transforming growth factor beta) supergene family, DPP (decapentaplegic protein) of Drosophila and Vg‐1 (vegetal protein) of Xenopus. Building upon this information we constructed a synthetic consensus gene to use as a probe to screen human genomic libraries. This resulted in the isolation of three interrelated genes. Among these were BMP‐2b an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
238
1
7

Year Published

1992
1992
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 538 publications
(248 citation statements)
references
References 46 publications
2
238
1
7
Order By: Relevance
“…It was purified from demineralized bovine bone matrix Luyten et al, 1989;Sampath et al, 1990), and human cDNAs Of eight different BMPs have been cloned Celeste et al, 1990;0zkaynak et al, 1990. The deduced amino acid sequences of BMPs have indicated that BMP-2 through BMP-8 are members of the TGF-~ superfamily Celeste et al, 1990;Ozkaynak et al, 1990Ozkaynak et al, , 1992, which is an important regulator of the differentiation of various types of Cells and organs (for review see Roberts and Sporn, 1990).…”
mentioning
confidence: 99%
“…It was purified from demineralized bovine bone matrix Luyten et al, 1989;Sampath et al, 1990), and human cDNAs Of eight different BMPs have been cloned Celeste et al, 1990;0zkaynak et al, 1990. The deduced amino acid sequences of BMPs have indicated that BMP-2 through BMP-8 are members of the TGF-~ superfamily Celeste et al, 1990;Ozkaynak et al, 1990Ozkaynak et al, , 1992, which is an important regulator of the differentiation of various types of Cells and organs (for review see Roberts and Sporn, 1990).…”
mentioning
confidence: 99%
“…Bone morphogenetic proteins (BMPs) 1 purified and cloned from demineralized bone matrix are the factors responsible for this ectopic bone formation (2)(3)(4)(5)(6)(7). The deduced amino acid sequence of BMPs indicates that they are members of the transforming growth factor-␤ (TGF-␤) superfamily (3, 6 -8).…”
mentioning
confidence: 99%
“…Considering the similarities between members of the TGF-p family, such a model may well be the basis for studies of other TGF-b isoforms and related proteins of the TGFp family. These include Mullerian inhibitory substance (MIS) [22] which causes regression of the Mullerian duCL during development OC the male embryo; the inhibinsiactivins [23], proteins which regulate FSH secretion by pituitary cells; the decapentaplegic gene product dpp of Drosopkih [24,25] which influences dorsoventral specification and morphogenesis of the imaginal discs; the Vg-1 gene product of Xwopus [26,27] which localizes to the vegetal pole of the egg; Vgr-1, the mammalian homologue of which is expressed during mouse embryogenesis; OP-1, the predicted human homologue of a major component of bovine osteogenic protein [29]; GDF-1 [30] another Vg-I related molecule which is expressed in early mouse embryos, and the bone morphogenetic proteins (BMPs) [31,32] which can induce de novo cartilage and bone formation. Besides their partial amino acid sequence homology to the TGF-p isoforms an outstanding feature of all these proteins is the strong positional conservation of cysteine residues, suggesting that these molecules may have similar 3D structures.…”
Section: Discussionmentioning
confidence: 99%